Punishing potential mothers? Evidence for statistical employer discrimination from a natural experiment - Jonas Jessen; Robin Jessen; Jochen Kluve (Labour Economics, 2019)
Before 2006, large firms in Germany were obliged to pay for the generous maternity protection of female employees, such that firms' expected costs depended on employees' gender and age. From 2006 onward, all firms paid for maternity protection by contributing to the statutory health insurance system, where the contribution depends only on the number of employees and their wages and is thus independent of gender and age. This had been the regulation for small firms already before the reform. Using data from linked employer-employee administrative records, we provide evidence that the reform was followed by an increase in female relative wages within large firms. This reform effect provides evidence for statistical employer discrimination in the pre-2006 setup.
Keywords: J31; J71; 330; Maternity protection; Statistical discrimination; Natural experiment